Channel Reform For Sustainable Development: A Case Study Of Strategic Restructuring Of Nokia (China) Ltd. - Zhou, Xin Jun (2005)
This paper will describe the market environment of China telecommunication industry. The paper tries to help companies understand China market through the description and analysis of China terminal's market.